2022
DOI: 10.1186/s12879-022-07742-3
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to COVID-19 vaccination among healthcare workers and the general population in Guinea

Abstract: Introduction The advent of the effective COVID-19 vaccine was the most eagerly expected worldwide. However, this hope quickly became hesitation and denial in many countries, including Guinea. Understanding the reasons for low vaccine coverage is essential to achieving herd immunity leading to disease control. This study aimed to comprehend the facilitators and barriers to the acceptance COVID-19 vaccine in Guinea. Methods The survey focused on heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Two of the 18 studies reported a positive perception [34,46] of the vaccine, while five of the 18 studies reported an overall negative perception [26,30,48,53,56] of the vaccine. According to the findings, two studies were diametrically opposed regarding attitudes and perceptions toward the vaccine.…”
Section: Attitudes and Perceptions Regarding Covid-19 Vaccines Among ...mentioning
confidence: 98%
See 3 more Smart Citations
“…Two of the 18 studies reported a positive perception [34,46] of the vaccine, while five of the 18 studies reported an overall negative perception [26,30,48,53,56] of the vaccine. According to the findings, two studies were diametrically opposed regarding attitudes and perceptions toward the vaccine.…”
Section: Attitudes and Perceptions Regarding Covid-19 Vaccines Among ...mentioning
confidence: 98%
“…The general adult population (aged ≥ 18 years) (n = 30) made up most of the study sample, while the general population comprised (n = 10). Three studies by Elhadi et al [28]; Gunawardhana et al [29]; and Toure et al [30] focused on the general population, including HCWs (n = 2) and pregnant women (n = 1). However, these sub-populations were not considered due to the abovementioned exclusion criteria.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied in four Guinean cities (Conakry, Mamou, Kankan and N'zérékoré). It has been carried out simultaneously as another great study [19] and used the same methodology and analytical approach.…”
Section: Study Settingmentioning
confidence: 99%